1998
DOI: 10.4315/0362-028x-61.4.425
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Hydrostatic Pressure, Time and Temperature of Pressurization and Pediocin AcH on Inactivation of Foodborne Bacteria

Abstract: High hydrostatic pressure, because it can kill microorganisms, is being investigated for potential use as a nonthermal food preservation method. The objective of this study was to determine the hydrostatic pressurization parameters, pressure, time, and temperature, and a bacteriocin that in combination would destroy 7 to 8 log cycles of pathogenic and spoilage bacterial populations. We suspended cells of Staphylococcus aureus, Listeria monocytogenes, Salmonella typhimurium, Escherichia coli O157:H7, Lactobacil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
74
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(79 citation statements)
references
References 0 publications
3
74
0
2
Order By: Relevance
“…Thus, pressure treatment at ambient temperature may in itself not be a safe pasteurization process under all conditions, and the combination of pressure with other hurdles seems to be necessary to increase safety. High pressure has been reported by several authors to increase the bactericidal spectrum of lysozyme and some bacteriocins against vegetative bacteria, and vice versa, these compounds increased the sensitivity of bacteria to pressure inactivation (9,13,16,17,21,25). This type of synergy offers an interesting perspective for the development of mild food preservation techniques for producing safe and high quality products.…”
mentioning
confidence: 98%
“…Thus, pressure treatment at ambient temperature may in itself not be a safe pasteurization process under all conditions, and the combination of pressure with other hurdles seems to be necessary to increase safety. High pressure has been reported by several authors to increase the bactericidal spectrum of lysozyme and some bacteriocins against vegetative bacteria, and vice versa, these compounds increased the sensitivity of bacteria to pressure inactivation (9,13,16,17,21,25). This type of synergy offers an interesting perspective for the development of mild food preservation techniques for producing safe and high quality products.…”
mentioning
confidence: 98%
“…The effect of HP treatments in combination with the lactoperoxidase system (9), lactoferrin and lactoferricin (21), lysozyme (12), and bacteriocins (12,15,17,23), on different foodborne pathogens and spoilage bacteria has been investigated. The effects of pressurization parameters and of the addition of pediocin AcH on the lethality of pathogenic and spoilage bacteria were studied by Kalchayanand et al (15), who recorded a higher reduction in the numbers of HP-injured E. coli O157:H7 cells in the presence of the bacteriocin.…”
mentioning
confidence: 99%
“…Published data have demonstrated that the application of specific additional hurdles such as antimicrobial peptides, the lactoperoxidase system, and phenolic compounds in combination with HHP treatments have synergistic inactivation effects (8,16,17,18,21,22,30,31,34,55,58). One of the most effective phenolic compounds is tertbutyl hydroquinone (TBHQ), which sensitizes some barotolerant Listeria monocytogenes strains to HHP (8,58).…”
mentioning
confidence: 99%